Stickler syndrome: case report - Vasco Carvalho; Diana Rita Oliveira; Marta Ribeiro Silva; Lídia Leite; Miguel Gonçalves Rocha; Liliana Pinheiro; Almerinda Pereira (Hygeia Press di Corridori Marinella, 2021)
Introduction: Stickler syndrome is a connective tissue disorder that can include midfacial underdevelopment and cleft palate, ocular findings (myopia, cataract, and retinal detachment), hearing loss that is both conductive and sensorineural and mild spondyloepiphyseal dysplasia and/or precocious arthritis. The phenotypical expression of Stickler syndrome is variable and typically associated with allelic heterogeneity. Description of case: Full-term newborn, cesarean delivery at 40 weeks. Fetal ultrasounds with orofacial malformation and mild hydronephrosis. The prenatal genetic screening test was negative. Fetal karyotype and array were normal with a male genomic profile. Fetal cerebral MRI showed brachycephalic skull configuration. At 10 minutes of life, the newborn had hypoxemia and was admitted to the Neonatal Intensive Care Unit. He had macrocephaly, but height and weight were adequate for the gestational age. At observation, he had axial hypotonia, craniofacial dysmorphia and posterior cleft palate. Mandibular hypoplasia and findings were compatible with connective tissue disease in 3D-CT. He had marked retinal choroiditis and pathological myopia and did not pass the neonatal hearing screening. Echocardiogram and capnography were normal. The hypothesis of Stickler syndrome was confirmed genetically with the COL11A1 gene mutation, variant c.2952+1G>T. Nowadays, at 13 months old, he maintains a multidisciplinary approach, with normal growth and psychomotor development. Conclusion: This case aims to illustrate a patient with a typical phenotype of a rare syndrome with posterior genetic confirmation. Multidisciplinary monitoring is essential to allow the timely diagnosis of complications associated with this syndrome (mitral valve prolapse or retinal detachment) and to assess the evolution of growth and psychomotor development.